2008
DOI: 10.1007/s00300-008-0452-x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the diatom-dominated microplankton summer assemblages in coastal waters from Terre Adélie to the Mertz Glacier, East Antarctica (139°E–145°E)

Abstract: In January 2004 the microplankton community from the coastal waters of Terre Adélie and Georges V Land (139°E-145°E) was studied. Results showed a diatomdominated bloom with chlorophyll a levels averaging 0.64 lg l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 28 publications
2
39
0
Order By: Relevance
“…Based on this study, the results show that F. cylindrus is able to acclimate to the new salinity and temperature conditions more rapidly than the other 2 species, potentially giving it a competitive advantage in the marine environment. This strongly supports its wide distribution as a generalist species and its prevalence throughout the Antarctic marine ecosystem (Lizotte 2001, Kopczynska et al 2007, Roberts et al 2007, Beans et al 2008. In contrast, Pseudonitzschia subcurvata showed a particular adaptation to meltwater characteristics, with a much lower level of photosynthetic plasticity for changes in salinity, temperature and light, perfectly matching the geographical environment where the species is known to be most abundant (Almandoz et al 2008).…”
Section: Discussionsupporting
confidence: 62%
“…Based on this study, the results show that F. cylindrus is able to acclimate to the new salinity and temperature conditions more rapidly than the other 2 species, potentially giving it a competitive advantage in the marine environment. This strongly supports its wide distribution as a generalist species and its prevalence throughout the Antarctic marine ecosystem (Lizotte 2001, Kopczynska et al 2007, Roberts et al 2007, Beans et al 2008. In contrast, Pseudonitzschia subcurvata showed a particular adaptation to meltwater characteristics, with a much lower level of photosynthetic plasticity for changes in salinity, temperature and light, perfectly matching the geographical environment where the species is known to be most abundant (Almandoz et al 2008).…”
Section: Discussionsupporting
confidence: 62%
“…This seemingly contradictory pattern between increased sea-ice cover and warmer temperature conditions during the Late Holocene can, however, be explained by the sea ice and temperature seasonal dynamics in the study area. The Late Holocene (i.e., Neoglacial period) was shown to experience greater late winter and early spring sea ice concentrations than the Mid Holocene (i.e., Hyperthermal period) [Crosta et al, 2008;Pike et al, 2009], which was favorable to the production of small Fragilariopsis species [Beans et al, 2008]. After sea ice disintegration, more intense wind activity during summer S, 135-145 E (100-pointrunning mean) .…”
Section: Resultsmentioning
confidence: 99%
“…Antarctic species successions and distribution have been investigated previously (Lizotte, 2001;Kopczynska et al, 2007;Almandoz et al, 2008;Beans et al, 2008), with some studies correlating observed distribution with physical and chemical oceanic parameters (Almandoz et al, 2008;Beans et al, 2008). Only a few however, have linked a species physiology and photosynthetic plasticity to its observed distribution and abundance (Kropuenske et al, 2009Petrou et al, 2011a;Petrou and Ralph, 2011).…”
Section: Lightmentioning
confidence: 99%